Pengaruh Etos Kerja Terhadap Kinerja Personel (Studi Satuan Perbekalan Detasemen Markas Tentara Nasional Indonesia Markas Besar Tentara Nasional Indonesia) - Haryanto, Bambang; Hariyadi, Ade Reza; Robby, Uchaimid Biridlo’I (FIA Unkris Press, 2023)
The research aims: 1) To find out and analyze the relationship of work ethic to the performance of personnel in the Indonesian Armed Forces Detachment Armed Forces Unit Headquarters of the Indonesian Armed Forces. 2) To find out the magnitude of the influence of the work ethic on the performance of personnel in the Indonesian Armed Forces Headquarters Detachment Unit. The research method is descriptive analysis with a quantitative approach. The sampling technique in this study used a simple random sampling technique, which is a random sampling technique without showing the existing strata in the population, so the sample in this study was 63 respondents with the error margin = 5%. Based on the results of the study, it can be concluded as follows: a) From the results of descriptive analysis, it is known that the results of the percentage score of each variable. The majority of respondents agreed with the work ethic carried out at the Indonesian Armed Forces Detachment Supplies Unit. While the majority of respondents agreed with the personnel performance implemented at the Indonesian Armed Forces Detachment Supplies Unit for personnel. b) While the analysis of the results of the study and discussion that there is a strong and significant positive relationship between work ethic and the performance of personnel in the Indonesian Armed Forces Detachment Armed Forces Unit Headquarters of the Indonesian Armed Forces is 0.738 so it is categorized strong. Then the magnitude of the effect produced by the work ethic on the performance of the personnel of the Indonesian Armed Forces Detachment Unit National Army Headquarters is 54.5% and the remaining 45.5% has an influence on other factors not included in this study